Construction of the ecological park complex project in Termez, Surkhandarya region (Journal of Architectural Design, 2022)
Today, the topic of ecology is one of the most important topics not only in our country, but all over the world. The same issue was raised at this year's G7 summit. It is noteworthy that environmental reforms are also being carried out in Uzbekistan. In this article, the author discusses the advantages of building an eco-park in Termez, Surkhandarya region.